MAKE IN INDIA AND BUSINESS ENVIRONMENT - Singh, Naib (International Journal For Research In Business, Management And Accounting, 2017)
Business environment has the great role in the development of any economy. Healthy business environment not only eases the business operations but also supports the growth process. Favourable business environment creates employment, generates opportunities for the entrepreneurship, contributes to the manufacturing process, provides base for the foreign trade. Government of India adopted liberalisation process in 1991 to give the boost to the Indian business. ‘Make in India’ has been designed to promote the environment for industrial growth of the country. This programme will support the economic growth of the country by utilizing the Indian talent, creating employment opportunities and facilitating the foreign direct investment in the fundamental sectors.